Microscopic analysis of polyimide nanocomposites aging mechanism exposed to partial discharges under high frequency voltage stress. Issue 2 (March 2020) - Asif, Muhammad; Li, Qingmin; Huang, Xuwei; Ren, Hanwen; Zian, Ding; Liu, Tao
Abstract: For the sake of investigating the influence of nanoparticles on the reduction in structural damage of neat polyimide (PI) and PI nanocomposites, scanning electron microscope (SEM) based microscopic study was conducted on unaged and aged pure PI and PI/TiO2 nanocomposite samples exposed to partial discharge activity under high frequency ac voltage stress. PI/TiO2 nanocomposites with 2, 3 and 5 wt.% were fabricated adopting in-situ polymerization technique. Partial discharge (PD) aging measurements were made and PD characteristic parameters were obtained to analyze the electrical performance of both neat PI and PI nanocomposites. Based on microscopic structural analysis, it was found that PI nanocomposite sample experienced less structural damage in contrast with neat PI. Smaller and lesser number of voids were found in PI/TiO2 nanocomposites than that of neat PI in result of PDs reduction in PI nanocomposite.